Using ddRADseq to assess the genetic diversity of in-farm and gene bank cacao resources in the Baracoa region, eastern Cuba, for use and conservation purposes - Ramirez-Ramirez, Angel Rafael; Mirzaei, Khaled; Menéndez-Grenot, Miguel; Clapé-Borges, Pablo; Espinosa-Lopéz, Georgina; Bidot-Martínez, Igor; Bertin, Pierre (Frontiers in Plant Science, 2024)
Baracoa region, eastern Cuba, hosts around 80 % of the country cacao (Theobroma cacao L.) plantations. Cacao plants in farms are diverse in origin and propagation with grafted and hybrid plants being the more common ones. Less frequent are plants from cuttings, TSH progeny and traditional Cuban cacao. A national cacao gene bank is also present in Baracoa with 282 cacao accessions either prospected in Cuba or introduced from other countries. A breeding and selection program associated to the gene bank started in the 1990's based on agro-morphological descriptors. The genetic diversity of the cacao resources in Baracoa has been poorly described, except for traditional Cuban cacao, affecting the proper development of the breeding program and the cacao planting policies in the region. To assess the cacao genetic diversity in the Baracoa region, we applied a new ddRADseq protocol for cacao using plants from the national cacao gene bank (CG) and cacao farms (CF). After data processing, 11,425 and 6,481 high quality SNPs were obtained from 238 CG and 135 CF plants, respectively. SNPs were unevenly distributed along the ten cacao chromosomes and laid mainly in non-coding regions of the genome. Population structure analysis based on these SNP datasets identified seven and four genetic groups in CG and CF samples, respectively. Clustering using UPGMA and principal component analysis mostly agree with population structure results. Cacao ancestry analysis revealed Amelonado as predominant, accounting for 49.22 % (CG) and 57.73 % (CF) of the total. Criollo, Contamana, Iquitos and Nanay ancestries were detected in both CG and CF samples while Nacional and Marañón backgrounds were only identified in CG. Genetic differentiation among CG (FST ranging from 0.071 -0.407) was higher than among CF genetic groups (FST: 0.093 -0.282). Genetic diversity parameters showed similar values for CG and CF samples. CG and CF genetic groups with the lowest genetic diversity parameters had the highest proportion of Amelonado ancestry. These results should contribute to reinforce the ongoing breeding and selection program and to update the current planting policies in cacao farms with impact in social and economic life of the region.